Income-Based Disparities in Financial Burdens of Medical Spending Under the Affordable Care Act in Families With Individuals Having Chronic Conditions - Wendy Yi Xu PhD; Sheldon M. Retchin MD, MSPH; Eric E. Seiber PhD; Yiting Li PhD (SAGE Publishing, 2019)
This study examined income-based disparities in financial burdens from out-of-pocket (OOP) medical spending among individuals with multiple chronic physical and behavioral conditions, before and after the Affordable Care Act's (ACA) implementation in 2014. Using the 2012-2015 Medical Expenditure Panel Survey data, we studied changes in financial burdens experienced by nonelderly U.S. populations. Financial burdens were measured by (1) high financial burden, defined as total OOP medical spending exceeding 10% of annual household income; (2) health care cost-sharing ratio, defined as self-paid payments as a percent of total health care payments, excluding individual contributions to premiums; and (3) the total OOP costs spent on health care utilization. The findings indicated reductions in the proportion of those who experienced a high financial burden, as well as reductions in the OOP costs for some individuals. However, individuals with incomes below 138% federal poverty level (FPL) and those with incomes between 251% and 400% FPL who had multiple physical and/or behavioral chronic conditions experienced large increases in high financial burden after the ACA, relative to those with incomes greater than 400% FPL. While the ACA was associated with relieved medical financial burdens for some individuals, the worsening high financial burden for moderate-income individuals with chronic physical and behavioral conditions is a concern. Policymakers should revisit the cost subsidies for these individuals, with a particular focus on those with chronic conditions.